Environmental enrichment modulates HPA axis reprogramming in adult male rats exposed to early adolescent stress. (November 2021) - Fan, Zhixin; Chen, Jie; Li, Ling; Wang, Hanzhang; Gong, Xiayu; Xu, Hanfang; Wu, Lili; Yan, Can
Highlights: Adolescent stress induced PTSD-like behaviors in adulthood. Adolescent stress enhanced HPA negative feedback inhibition in adulthood. Adolescent stress increased GR expression in the hypothalamus and hippocampus. Environmental enrichment ameliorated behavioral abnormalities and HPA dysregulation. Abstract: Exposure to early stressful events increases susceptibility to post-traumatic stress disorder (PTSD) in adulthood, in which the hypothalamic-pituitary-adrenal (HPA) axis plays a crucial role. Studies have found that environmental enrichment (EE) mitigates the detrimental outcomes of early adversity. However, the HPA-related mechanism remains unclear. In this study, we used the single prolonged stress (SPS) paradigm to explore the long-term effects of early adolescent stress on behavior, HPA axis activity, as well as expression levels of the glucocorticoid receptor (GR), mineralocorticoid receptor (MR), corticotropin-releasing hormone receptor 1 (CRF1R) and CRF2R in the hypothalamus and hippocampus. Meanwhile, the protective effects of EE intervention were examined. We found that adult male rats exposed to adolescent stress showed reduced locomotor activity, increased anxiety-like behaviors, enhanced contextual fear memory, elevated basal plasma ACTH levels, and enhanced HPA negative feedback inhibition, as indicated by decreased plasma ACTH levels in the dexamethasone suppression test (DST). Furthermore, EE normalized the behavioral abnormalities and enhanced HPA negative feedback in stressed rats, possibly through down-regulating GR expression in the hippocampus and hypothalamus. These findings suggested that EE could ameliorate adolescent stress-induced PTSD-like behaviors and aberrant reprogramming of the HPA axis, reducing the risk of developing PTSD in adulthood.